The assessment strategy: An elusive curriculum structure - Scholtz, D (South African Journal of Higher Education, 2016)
The unprecedented scale of curriculum development in response to national imperatives has prompted questions on curriculum approaches and strategies. The focus of this article is on how four departments conceived assessment during the recurriculation of diploma qualifications. The findings suggest that assessment is approached from a technicist perspective and compliance with principles of good assessment practice. In response to the findings, the purpose and structure of an assessment strategy as an over-arching mechanism to inform and guide assessment practices at programme level are explored. It is argued that a collaborative, programme-specific assessment strategy creates an opportunity for synergy to achieve the purpose of the qualification and for holistic graduate development.